2013
DOI: 10.1111/aen.12032
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of biomass from body length and width for tropical rainforest canopy invertebrates

Abstract: Accurate estimates of invertebrate biomass are essential for quantifying community structure, food web dynamics and energy flow in terrestrial ecosystems. In this paper, length‐mass and length × width‐mass regressions were carried out for 18 invertebrate taxonomic groups collected from the canopy of an Australian tropical rainforest. In an additional analysis, invertebrates were divided among seven body shape categories based on the ratio of body length to body width (from short and squat to long and thin) in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
27
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 26 publications
0
27
0
Order By: Relevance
“…& Enquist, 2009;Packard, 2009;Xiao et al, 2011). Previous studies estimating insect length-weight scaling relationships used quadratic functions for terrestrial insects (Sage, 1982) or log-log linear functions for Australian canopy insects (Wardhaugh, 2013). Xiao et al (2011) recommend using linear functions over nonlinear functions when data are log-normal, as ours were.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…& Enquist, 2009;Packard, 2009;Xiao et al, 2011). Previous studies estimating insect length-weight scaling relationships used quadratic functions for terrestrial insects (Sage, 1982) or log-log linear functions for Australian canopy insects (Wardhaugh, 2013). Xiao et al (2011) recommend using linear functions over nonlinear functions when data are log-normal, as ours were.…”
Section: Discussionmentioning
confidence: 85%
“…There has been a lively debate on the statistical methods used for allometric scaling functions for animals in general (Kerkhoff & Enquist, ; Packard, ; Xiao et al ., ). Previous studies estimating insect length–weight scaling relationships used quadratic functions for terrestrial insects (Sage, ) or log–log linear functions for Australian canopy insects (Wardhaugh, ). Xiao et al .…”
Section: Methodsmentioning
confidence: 99%
“…As more than 97% of the variance in body mass was described by length, width, taxonomic group, and geographic region, the benefit of adding body height would unlikely outweigh the added workload. Indeed, previous studies have shown that including body shape (i.e., body length and width) instead of taxonomy lead to more accurate body mass estimates at the order level, but not at higher taxonomic resolution (Gruner, ; Wardhaugh, ). Our results strongly support the finding that the accuracy in predicting body mass improves with adding further morphological traits, which are related to volume, in addition to body length for scaling relationships conducted at the order level.…”
Section: Discussionmentioning
confidence: 99%
“…Length-mass regressions have proven to be a powerful tool to predict body mass based on body length measurements (Benke, Huryn, Smock, & Wallace, 1999;Gruner, 2003;Johnston & Cunjak, 1999;Rogers, Buschbom, & Watson, 1977;Schoener, 1980;Wardhaugh, 2013), which are in some cases, easier to obtain than direct measurements of body mass. For living or particularly small organisms, direct measurement of body mass can be difficult and time-consuming.…”
mentioning
confidence: 99%
See 1 more Smart Citation